What is trustworthiness and what drives it? - James C. Cox; Rudolf Kerschbamer; Daniel Neururer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
This paper reports the results of experiments designed to isolate the impact of various combinations of the following motives on trustworthiness: (i) unconditional other-regarding preferences - like altruism, inequality aversion, quasi-maximin, etc.; (ii) deal-responsiveness - reacting to actions that allow for a mutual improvement by adopting behavior that implies a mutual improvement; (iii) gift-responsiveness - reacting to choices that allow the trustee to obtain an improvement by adopting actions that benefit the trustor; and (iv) vulnerability-responsiveness - reacting to the vulnerability of the trustor by adopting actions that do not hurt the trustor. Our results indicate that - besides unconditional other-regarding preferences - vulnerability-responsiveness is an important determinant of trustworthiness even in cases where the vulnerability of the trustor does not come together with a gift to the trustee. Motivated by our empirical findings we provide formal definitions of trust and trustworthiness based on revealed willingness to accept vulnerability and the response to it.
Keywords: C70; C91; D63; D64; 330; trustworthiness; trust; trust game; investment game; deal-responsiveness; gift-responsiveness; vulnerability-responsiveness; generosity; reciprocity